Guiding focus group discussions on varietal diversification and adaptation to climate change in East Africa - Gevel, Jeske M.J, van de; Bijdevaate, M.; Mwenda, P.; Morimoto, Y.; Fadda, Carlo; Bioversity International (2014)
This training manual presents the objectives and tools used in focus group discussions for the survey on socio-economic and environmental factors that lead to farmers’ vulnerability as part of a joint project entitled “Linking genetic vulnerability to loss of resilience to adapt to climate change”. This manual provides suggestions for field coordinators and researchers who are organizing focus group discussions in farming communities. It serves as a training manual for facilitators and allows them to familiarize themselves with the objectives of the focus groups and the tools used to collect data. The methodology was developed and tested in CCAFS benchmark sites of Nyando and Makueni in Kenya and in Hombolo district in Tanzania.